Diabetic retinopathy as a predictor of cardiovascular morbidity and mortality in subjects with type 2 diabetes - Barrot, Joan; Real, Jordi; Vlacho, Bogdan; Romero-Aroca, Pedro; Simó, Rafael; Mauricio, Didac; Mata-Cases, Manel; Castelblanco, Esmeralda; Mundet-Tuduri, Xavier; Franch-Nadal, Josep (Frontiers in Medicine, 2022)
This study aimed to evaluate the predictive value of diabetic retinopathy (DR) and its stages with the incidence of major cardiovascular events and all-cause mortality in type 2 diabetes mellitus (T2DM) persons in our large primary health care database from Catalonia (Spain). A retrospective cohort study with pseudo-anonymized routinely collected health data from SIDIAP was conducted from 2008 to 2016. We calculated incidence rates of major cardiovascular events (coronary heart disease, stroke, or both-macrovascular events) and all-cause mortality for subjects with and without DR and for different stages of DR. The proportional hazards regression analysis was done to assess the probability of occurrence between DR and the study events. About 22,402 T2DM subjects with DR were identified in the database, and 196,983 subjects without DR. During the follow-up period among the subjects with DR, we observed the highest incidence of all-cause mortally. In the second place were the macrovascular events among the subjects with DR. In the multivariable analysis, fully adjusted for DR, sex, age, body mass index, tabaco, duration of T2DM, an antiplatelet or antihypertensive drug, and HbA1c, we observed that subjects with any stage of DR had higher risks for all of the study events, except for stroke. We observed the highest probability of all-cause death events (adjusted hazards ratios-AHR: 1.34, 95% CI: 1.28; 1.41). In conclusion, our results show that DR is related to coronary heart disease, macrovascular events, and all-cause mortality among persons with T2DM.